1990
DOI: 10.1002/ijc.2910460331
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of anchorage‐independent growth of a human adrenal carcinoma cell line by endogenously produced basic fibroblast growth factor

Abstract: We have previously observed that a human adrenal carcinoma cell line (SW-13) produces autocrine growth factors that enhance the ability of these cells to clone in soft agar. We now show that a basic FGF-like protein is found in SW-13 lysates and stimulates SW-13 colony growth. Basic FGF (bFGF) was identified in SW-13 lysates by both its chromatographic behavior on heparin-Sepharose and its reactivity with an antibody specific for bFGF. Incubation of lysates with antibodies specific for bFGF abolished their abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Fibroblast growth factors 12 and 14 are localized within two of the amplified regions, namely, 3q28qter and 13q34, respectively. It has previously been shown that the adrenocortical carcinoma cell line SW13 produces autocrine fibroblast growth factors mediating anchorage-independent growth (Corin et al, 1990). CGH of SW13 revealed amplification of the chromosomal segment harboring FGF12.…”
Section: Discussionmentioning
confidence: 93%
“…Fibroblast growth factors 12 and 14 are localized within two of the amplified regions, namely, 3q28qter and 13q34, respectively. It has previously been shown that the adrenocortical carcinoma cell line SW13 produces autocrine fibroblast growth factors mediating anchorage-independent growth (Corin et al, 1990). CGH of SW13 revealed amplification of the chromosomal segment harboring FGF12.…”
Section: Discussionmentioning
confidence: 93%
“…Fibroblast growth factors 12 and 14 are localized within two of the amplified regions, namely, 3q28–qter and 13q34, respectively. It has previously been shown that the adrenocortical carcinoma cell line SW13 produces autocrine fibroblast growth factors mediating anchorage‐independent growth (Corin et al, 1990). CGH of SW13 revealed amplification of the chromosomal segment harboring FGF12 .…”
Section: Discussionmentioning
confidence: 99%
“…Nestes segmentos encontram-se os loci dos fatores de crescimento de fibroblasto (FGF) 12 e 14, respectivamente [34] . As células SW13 produzem autocrinamente FGFs que conferem o crescimento independente de ancoragem (capacidade de proliferar, formar colônias em ágar) [37] . Especulase que a amplificação do 3q28-qter seja responsável pela produção autócrina do FGF12 por essas células e, conseqüentemente, pelo crescimento independente de ancoragem [34] .…”
Section: Tumorigênese E Marcadores De Carcinoma Do Córtex Da Supra-renalunclassified